Sustainable Improvement of Marine Clay Using Recycled Blended Tiles - Al-Bared, M.A.M. (Springer International Publishing, 2018)
The usage of recycled material for improving problematic soil as a construction and pavement material has been a sustainable interest. Recycled blended tiles (RBT), a waste from ceramic tiles factories containing high amount of sodium and magnesium, was used as a soil stabilizer for marine clay improvement in this study. This research investigated the effects of sizes and percentages of RBT on the physical and strength properties, which included particle size distribution, Atterberg limits, compaction, and unconfined compressive strength (UCS) of marine clay. Microstructural characterization, including the scanning electron microscopic, energy dispersive X-ray spectroscopy, and X-ray diffraction was conducted on both untreated and treated marine clay-RBT samples to examine the mechanism of strength development. The addition of RBT reduced the water holding capacity, which then caused the reduction in soil plasticity (from 18 to 11) and optimum water content (from 20 to 16) along with the increase in peak dry density (from 1.66 to 1.74 Mg/m3). The UCS of marine clay increased from 50 to almost 220 kPa. The optimum RBT contents, providing the highest UCS, were at 20 and 30 for 0.063 mm RBT and 0.15 mm RBT, respectively. The UCS improvement of treated marine clay is attributed to the formation of cementation compounds, mainly aluminum magnesium silicate hydrate (AâMâSâH). The outcome of this research will allow the use of RBT as a low-carbon soil stabilizer across civil engineering applications. Â© 2018 Springer International Publishing AG, part of Springer Nature